Selecting flagship species to solve a biodiversity conservation conundrum - Jie Qian; Huifu Zhuang; Weikang Yang; Yifeng Chen; Shilong Chen; Yanhua Qu; Yuanming Zhang; Yongping Yang; Yuhua Wang (Plant Diversity, 2020)
The difficulty of effectively monitoring and managing the environment to conserve biodiversity is as yet an unsolved conundrum. A project of the Chinese Academy of Sciences has concluded that progress can be made through the use of flagship species selected using criteria drawn from conservation biology, ecosystem function, socio-economics, and cultural importance. Inclusion of the latter three criteria will help attract and maintain the commitment of the public to play full parts in carrying out any conservation measures needed. A system is proposed for scoring species to select those that are most suitable as flagships. This method can be used regardless of the size of the area chosen for attention, whether it is a region, a country, or a particular protected area.